2013
DOI: 10.1016/j.ajpath.2013.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative Actions of T-Type Calcium Channel Inhibition in Thy1 Nephritis

Abstract: Aberrant proliferation of mesangial cells (MCs) is a key finding in progressive glomerular disease. TH1177 is a small molecule that has been shown to inhibit low-voltage activated T-type Ca(2+) channels (TCCs). The current study investigates the effect of TH1177 on MC proliferation in vitro and in vivo. The effect of Ca(2+) channel inhibition on primary rat MC proliferation in vitro was studied using the microculture tetrazolium assay and by measuring bromodeoxyuridine incorporation. In vivo, rats with Thy1 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
18
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 22 publications
8
18
2
Order By: Relevance
“…This agent inhibits the proliferation of cultured human and rat MCs in vitro and is also a potent antiproliferative agent in prostate cancer cells in vitro and in vivo [3,4]. We have reported that administration of TH1177 to rats with acute Thy1 nephritis reduces glomerular injury and glomerular cell proliferation in this short-term disease model [5]. This finding supports the hypothesis that TH1177 may be of benefit in renal diseases that involve excess mesangial cell proliferation.…”
Section: Introductionsupporting
confidence: 64%
“…This agent inhibits the proliferation of cultured human and rat MCs in vitro and is also a potent antiproliferative agent in prostate cancer cells in vitro and in vivo [3,4]. We have reported that administration of TH1177 to rats with acute Thy1 nephritis reduces glomerular injury and glomerular cell proliferation in this short-term disease model [5]. This finding supports the hypothesis that TH1177 may be of benefit in renal diseases that involve excess mesangial cell proliferation.…”
Section: Introductionsupporting
confidence: 64%
“…However, EPA did not reduce CD68-positive macrophage infiltration into glomeruli and failed to reduce proteinuria, suggesting that inhibition of macrophage infiltration in the glomerulus is important for reducing proteinuria and glomerular injury in the rat Thy-1 model. Indeed, many studies (3,28) have shown that reductions of proteinuria and glomerular injury are related to the reduction of macrophages in glomeruli. In our study, the number of CD68-positive macrophages in glomeruli was not decreased by treatment with alogliptin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Three-micrometer sections were stained with periodic acid-Schiff reagent and counterstained with hematoxylin. Quantification of renal histology was performed as previously described (3). Briefly, 30 glomeruli/section were scored using the following system: 0 ϭ normal appearance, 1 ϭ mesangial expansion and/or hypercellularity, and 2 ϭ microaneurysms, necrosis, capsular hemorrhage, or matrix or cellular crescents.…”
Section: Animalsmentioning
confidence: 99%
“…Deparaffinized sections were stained with Periodic Acid-Schiff to examine the pathological changes under light microscopy. The degree of renal impairment was semi-quantitatively and double-blindly scored by two pathologists following a published scoring system [9]. We randomly selected 10 separate fields for each specimen to evaluate the lesions (400× magnification) and averaged the values for the histological score.…”
Section: Methodsmentioning
confidence: 99%